1997
DOI: 10.4315/0362-028x-60.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Farm Manure-Handling Practices on Escherichia coli O157 Prevalence in Cattle

Abstract: Thirty-six dairy herds in Idaho, Oregon, and Washington were selected on the basis of cattle housing and manure-handling practices. Approximately 60 fecal samples from heifers were collected monthly in each herd for 6 months and cultured for Escherichia coli O157. One hundred seventy-nine of 12,664 (1.41%) individual fecal samples from 27 of the 36 herds (75%) were culture positive for E. coli O157. Within-herd prevalence ranged from 0% to 5.5% with a strong clustering toward the lower end of this range. A ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 0 publications
5
56
1
Order By: Relevance
“…The presence and persistence of STEC, and in particular of EHEC O157, in these products may therefore be an important factor in the initial infection and re-infection of cattle [79,92]. On the contrary, when cattle manure or slurry are applied on farmland in the production of food crops that are to be consumed in the raw or minimally processed state, appropriate handling of these products is necessary to control the spread of potentially present STEC and limit the risks of human infection [66,77]. Cattle manure composting before its spread onto land may reduce the risk of transmission of STEC through contaminated vegetables [80,81,101].…”
Section: Persistence In Faeces and Manurementioning
confidence: 99%
“…The presence and persistence of STEC, and in particular of EHEC O157, in these products may therefore be an important factor in the initial infection and re-infection of cattle [79,92]. On the contrary, when cattle manure or slurry are applied on farmland in the production of food crops that are to be consumed in the raw or minimally processed state, appropriate handling of these products is necessary to control the spread of potentially present STEC and limit the risks of human infection [66,77]. Cattle manure composting before its spread onto land may reduce the risk of transmission of STEC through contaminated vegetables [80,81,101].…”
Section: Persistence In Faeces and Manurementioning
confidence: 99%
“…Hancock et al (1994) reported a tentative association between applying slurry to grazing land and the E. coli O157:H7 infection status of the herd. Subsequent studies, however, reported no association between manure application to pastures or forage crops for cattle and E. coli O157:H7 fecal shedding by cattle Hancock et al 1997b). More recently, a study by Bolton et al (1999) indicated that current waste management practices such as spreading manure on pastureland may increase the carriage rate of E. coli O157:H7 in herds.…”
Section: Manurementioning
confidence: 99%
“…2,10,13 In North America, only 2 cases of infection by this organism have been documented in domestic animals (a dog and a goat), both from Oregon. 11,12 The infection, however, is not uncommon in wildlife and has been reported in mice, moles, rats, rabbits, ground squirrels, weasels, martens, minks, armadillos, wallabies, skunks, and opossums.…”
Section: Pulmonary Adiaspiromycosis In Raccoons (Procyon Lotor) From mentioning
confidence: 99%